Numerical Modeling and Experimental Validation of TiC Nanoparticle Distribution During the Ultrasonic Casting Process of 2219 Aluminum Matrix Nanocomposites - Yi-Long, Yang; Yun, Zhang; Hao-Ming, Zhang; Xu-He, Liu (Frontiers in Materials, 2022)
In this work, a two-dimensional model of 0.9 wt% TiC nanoparticle-reinforced 2219 aluminum nanocomposites fabricated by a high-intensity ultrasonic casting technique was established. The multiphase computational fluid dynamics (CFD) ultrasonic cavitation model accounting for heat exchange, turbulent flow, and the variable interaction between nanoparticles and melts by using Ansys’s Fluent Dense Discrete Phase Model (DDPM) was used to investigate the TiC nanoparticle distribution in 2219 aluminum melts. The results of the simulation calculation showed that the TiC nanoparticle distribution in aluminum melts was influenced by the ultrasonic power. An appropriate ultrasonic power has a promoting effect on the dispersion of nanoparticles. The number of nanoparticles in the center position of the molten pool was less than that in the edge position of the molten pool due to the influence of ultrasonic streaming. Moreover, the effectiveness and accuracy of the simulation were verified by experiments. Optical microscopy (OM) revealed that the grain size in the center position was smaller than that in the edge position. TEM and SEM were used to observe the TiC nanoparticle distribution. Nanoparticles in the center position were more evenly distributed than those in the edge position. There were more nanoparticles agglomerating in the edge position. The experimental results were basically consistent with the simulation results. In general, the nanoparticles were evenly distributed in the nanocomposites.